ONLINE REAL-LIFE SITUATION QUESTIONNAIRES TO DEVELOP TOP-DOWN READING SKILL - Adelina, Erni; Hutabarat, Peny Meliaty (Jurnal Vokasi Indonesia, 2023)
The top-down reading approach is generally applied in upper-intermediate to advanced ESL classes. The approach is thought to be too overwhelming for students who are at pre-intermediate, intermediate, or even beginner levels. Instructors may think that involving students’ background information or past knowledge in a passage topic will be burdensome for ESL students in a lower-level class. As a matter of fact, many students in any level of English class were experiencing or questioning the same issues in their routines. Separating students’ past knowledge from reading activity is impossible. This study was conducted to find out students’ past experience or prior knowledge on one issue and observe whether the reading passage might change or strengthen their ideas toward something they had in mind before the reading by filling out online pre- and post-questionnaires. The reading passage also contains follow-up questions as tools for students to measure their comprehension. The results of this study have shown that there are tendencies to alter ideas after the reading activity, based on post-activity questionnaires. In addition, performing the questions from the passage has provided information on students’ satisfying results in comprehension by calculating how many questions they answered correctly.